p75 NTR expression is induced in isolated neurons of the penumbra after ischemia by cortical devascularization - Angelo, María Florencia (2009)
The p75 neurotrophin receptor (p75NTR) is involved in neuronal functions going from induction of apoptosis and growth inhibition to the promotion of survival. p75NTR expression is induced in central nervous system (CNS) by a wide range of pathological conditions where it seems to have a main role in neuronal death and axonal growth inhibition. The cellular mechanisms driving p75NTR expression in cell lines and primary neurons in culture depend on Sp1-induced transcription (Ramos et al., 2007, J. Neurosci 27:1498). In this study we analyzed the spatio-temporal profile of p75NTR expression after a localized ischemic lesion in the rat brain induced by cortical devascularization (CD). Our results showed that p75NTR expression occurred in isolated neurons of the ischemic penumbra. The p75NTR+ neurons presented morphological alterations and active caspase-3 staining. Some of these p75NTR+ neurons were also positive for sortilin. The peak of p75NTR expression was localized 3 days after the lesion (3DPL), while abundance of Sp1 transcription factor increased from 3 to 14DPL on the lesioned hemisphere. In primary cortical neurons, we demonstrated that p75NTR expression is induced by excitotoxic stress and correlated with increased Sp1 abundance. We conclude that p75NTR expression is localized in selected neurons of the ischemic penumbra and these neurons are probably condemned to apoptotic cell death. In primary neuronal culture is clear that excitotoxity and Sp1 are involved in induction of p75NTR expression, although in vivo some additional mechanisms are likely to be involved in the control of the p75NTR expression in specific neurons in vivo.